High expression of TRIM24 predicts worse prognosis and promotes proliferation and metastasis of epithelial ovarian cancer - Liwei Zhang; Hong Chen; Baijuan Ding; Wei Jiang (BMC, 2022)
Abstract Background Tripartite Motif-Containing 24 (TRIM24) is a member of the tripartite motif family. TRIM24 is claimed aberrantly activated in a number of cancers, such as breast cancer, prostate cancer and lung cancer. However, the expression of TRIM24 in epithelial ovarian cancer (EOC) and its relationship with prognosis remain unclear. In this study, we investigated the expression pattern and underlying clinical significance of TRIM24 in EOC. Results Data from Oncomine and immunohistochemistry of tissue samples demonstrated that TRIM24 expression was obviously elevated in ovarian carcinoma compared with normal ovary tissues. Elevated TRIM24 expression was closely correlated with serum CA-125 (P = 0.0294), metastasis (P = 0.0022), FIGO (International Federation of Gynecology and Obstetrics) stage (P = 0.0068) and Ki-67 level (P = 0.0395). Kaplan-Meier survival analysis found that TRIM24 expression increased inversely with the clinical prognosis of patients with EOC. Moreover, colony formation and CCK-8 assays showed that TRIM24 promoted EOC cell growth, and tumorigenic experiments in nude mice showed that TRIM24 knockdown inhibited tumor growth in vivo. The Spearman's correlations revealed that the expression of TRIM24 was significantly correlated with levels of Ki-67 (P = 0.01), at a correlation coefficient of 0.517. Wound-healing and transwell migration assays demonstrated TRIM24 facilitated cell migration. Mechanism studies showed that TRIM24 could promote the phosphorylation level of Akt and the process of EMT. Conclusion Our results confirmed that TRIM24 could predict poor prognosis of EOC patients and promote tumor progression by regulating Akt pathway and EMT. TRIM24 may be used as a new prognostic marker for EOC and may provide a new strategy for targeted therapy of epithelial ovarian cancer.